(untitled) (Research, Society and Development, 2022)
Digital marketing emerged with the beginning of the internet and has been growing more and more, being an important tool for selling products and services, and with the emergence of Covid-19 it has become even more fundamental. The present research aims to present the usability and importance of digital marketing for companies during the Covid-19 pandemic period. This article is a qualitative narrative review of the literature. Marketing consists of a social process that seeks the needs of a certain group, in order to understand and satisfy them, digital marketing has opportunities to have more targeted, intelligent and effective communication, generating greater customer relationships, in addition to agility in the programming and delivery of campaigns. The avalanche of uncertainties caused by Covid-19 that brought to light the importance of implementing digital marketing in this pandemic should be part of the administrative routine of companies since the digital tool promotes an option for the dissemination of products and new ways of working. It is possible to observe that although the losses of Covid-19 have been disastrous, the establishments and have adapted to the new reality had the opportunity to reinvent themselves. Thus, for future studies, it is suggested that field research be carried out using documentary research questionnaires from companies in order to evaluate the use of digital marketing in a comparative way before, during and after the pandemic.